Reconstructing Electronic Legislation to Strengthen Public Accountability: Lessons from Indonesia - Kishan, Marcelino Ceasar (Jurist-Diction, 2025)
This paper examines the role of public participation in electronic legislation, with particular reference to the Indonesian context. It assesses whether electronic legislation can operate as a mechanism for strengthening legislative accountability. The study employs a normative legal method, supported by doctrinal analysis of positive law, to evaluate the relationship between normative expectations and their legal realization. The findings indicate that the current framework for electronic legislation lacks comprehensive norms on public participation, resulting in fragmented and inconsistent standards. The absence of binding rules undermines accountability and weakens the democratic quality of lawmaking. To address this gap, the paper proposes a reconstruction of participation norms through a re-evaluation of the concept of electronic legislation. This reconstruction binds all actors to participation requirements. It also compels legislatures to engage actively in the design and implementation of electronic systems. In turn, it reinforces accountability, transparency, and inclusiveness in the legislative process.